Implementasi Automation Testing End-to-End Menggunakan Cypress pada Web E-Conference Parisada serta Evaluasi Efisiensi Pengujian - Raditya Aria; Eri Haryanto; Ryan Ari Setyawan (Infotek: Jurnal Informatika dan Teknologi, 2026)
Manual testing on interactive applications such as web e-conferences often faces constraints in the form of human error and long execution durations, especially in repetitive regression processes. This research aims to implement automated end-to-end (E2E) testing using the Cypress framework and evaluate the level of testing time efficiency on the Parisada platform. The research methodology includes designing core functionality scenarios covering the authentication process, system navigation, meeting room creation, and communication session termination. Testing was conducted through three trials (P1, P2, P3) to simulate various inhibiting variables, such as unstable network latency and user familiarity levels with the application interface. The results showed that all automated testing scenarios successfully achieved a 100% pass rate. In terms of efficiency, the use of Cypress significantly reduced the execution duration from an average of 60.0 seconds in manual testing to only 23.67 seconds in automated testing. Data analysis indicates an average time efficiency increase of 60.55%. Automated testing also proved to be more consistent and reliable in dealing with technical fluctuations compared to manual testing. In conclusion, the transition to automation testing using Cypress has proven highly effective in accelerating the quality assurance (QA) cycle and maintaining continuous software functionality stability on the Parisada application.